1298 Ergonomic analysis of electronic sports players – unravelling risks – post-graduation in ergonomics. (24th April 2018) - Oliveira, TA; Costa, P; de Araújo, HM; de Toledo, CM; Primo, GF
Abstract : Introduction: Performed Ergonomic Analysis of Work (AET) with professional players of Electronic Sports (mode: League of Legends). It is known through social networks, interactive newspapers and television broadcasters that the modality is on the rise and that it also brings some evidence and difficulties related to pain in the wrists of athletes. The pains in the fist are in the area of Physical Ergonomics, but can not be considered the origin of the cause. We also know that the work tool of the players is the computer, so the second point to be studied is in the field of Cognitive Ergonomics, where we approach topics related to decision making, memory, reasoning, perception, human-machine interaction, reflexes.Ergonomics has its three established pillars: Physical, Organisational and Cognitive Ergonomics, and we have done the work focused on this perception of the existing risks. Objective: It is understood ergonomics as adaptation of work to man, application of scientific knowledge necessary to design tools, machines and devices that can be used with maximum comfort, safety and effectiveness (FALZON, 2007). The purpose of the work is not different from those principles that the author puts forward. The proposal, in addition to providing a work environment that minimises problems related to wrist pain, understands the cognitive processes present in the athletes' daily lives. Analysis methodology: For methodology we will use the points predicted in the AET: demand, analysis of the task, analysis of the activity, diagnosis, proposals and implementations. Methods by observing and elaborating questions pertinent to what you are encountering. Application of ergonomic tools and installation of Mouse Metre software, measuring the intensity of clicks per second on the mouse (direct button and left button), mouse movement on the desktop, clicks on the keyboard. A questionnaire with 6 players was carried out. 3 perform gym and 1 practice race. Conclusion: The study aims to contribute to the community of electronic sports and ergonomics, because it is a relatively new area for the field of work, it is interesting that there is knowledge about the aspects related to the ergonomics involved in the activity of the athletes. The analysis is based on ergonomics as a whole (cognitive, organisational and physical) – and it was evidenced that for many hours sitting, in front of computer with inadequate posture (even by the body's need to modify positions for its comfort), keyboard use Intensely, and stare at the screen to perform the avatar commands correctly, with reflexes and at the right time. It is noticed that almost 60% of the day of them they spend playing (they are seated during 13 hours of the day), They perform wrist movements and very intense hands (both by typing and by clicking) and identify pains in the shoulders, forearms, wrists and cervical, most common on the side that use the mouse for the most part (dominant member). Players with their own chair feel less discomfort in the body, players with more complaints of pain are those who do not have support in the arm chair. The cognitive part they discuss game strategy, in-game communication, decision-making to achieve in-game goals are in direct interactivity with the game interface (map, skills, goal time, gold conquered); Players may know part of the habilities of the 137 players available in the game – where each champion/player has an average of 5 skills – in a total of 500 skills, but there are no reports of player complaints about this seemingly idiosyncratic use of cognitive skills.